EFEK MODIFIKASI PERMUKAAN KARBON AKTIF MONOLIT TERHADAP SIFAT FISIS DAN ELEKTROKIMIA SEL SUPERKAPASITOR - Yanti, Sri; Taer, Erman; ', Sugianto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Surface modification of activated carbon monolith electrode   for  a  supercapacitor cell from rubber wood has successfully been made by two activation methods. Physical activation  was perfomed  using  CO2  gas  at a temperature of  800oC, and chemical  activation used  3  M  KOH  and  3  M  NaOH  as activation  agents. This study used two kinds  of activated agents, namely COK for KOH activated agent and CON for NaOH activated agent. Both  activation methods yielded different physical and electrochemical properties. The  physical properties  that were analyzed  were  density ,   surface  morphology,  and  BET  surface area,  whereas  the electrochemical properties were specific capacitance, specific energy,  and specific power.  N2  gas  isothermal  adsorption  showed  a BET  surface area  of  577.52  m2g-1 and  441.45  m2g-1. Meanwhile,  the electrochemical  properties obtained of sample were  the specific  capacitance  values  of  103.65  Fg-1 and  83.45  Fg-1for  CON  and COK, respectively . Based on all obtained data and their analysis, it was concluded that KOH   activators  resulted  the  electrochemical properties  better  compared tothose of  NaOH activators.